Integrated Financial Management System and Financial Control in Uganda: A Review of Issues and Concerns - Akidi, Stella; Okuna, Victor; Mwesigwa, David (American Journal of Strategic Studies, 2024)
Purpose: This study aimed to analyze the issues and concerns within the government’s policy on Integrated Financial Management System as a financial control in Uganda. Methodology: The study adopted a literature review approach in which the reviewers identified, assessed and studied obtainable literature from a variety of sources majorly on line and from the government libraries. Results: The review indicated that IFMS contributed to financial control in many ways, such as enhanced internal controls, improved budget execution and control as well as strengthened cash and debt management. However, a number of challenges emerged mid-way viz, resistance to change, inadequate user training, technological challenges and weak project management. To counter, the challenges there is need to strengthen change management strategies, enhance capacity building and training, improve technological infrastructure and integration, strengthen governance, and ensure strong political commitment and support. Unique contribution to theory, practice and policy: This review contributes to the understanding and further appraisal of the government policy on IFMS learning from its successes as a way of thwarting the emerging threats and failures. The review encourages for a deliberate investment in comprehensive training programs for users at all levels to ensure they understand FMIS functionalities and can utilize them effectively; regularly reporting on the IFMS performance and sharing lessons learned with key stakeholders so as to promote transparency, accountability, and continuous improvement; Developing a robust and resilient IT infrastructure and establishing robust data quality assurance processes to validate the accuracy and reliably of information entered into IFMS, ensuring decision making is based on reliable data.